2020
DOI: 10.2147/lctt.s254146
|View full text |Cite
|
Sign up to set email alerts
|

<p>Correlation of Immune-Related Adverse Events and Effects of Pembrolizumab Monotherapy in Patients with Non-Small Cell Lung Cancer</p>

Abstract: Purpose The effects of immune checkpoint inhibitors have been reported to be linked with immune-related adverse events (irAEs). In patients with advanced non-small-cell lung cancer, who tested positive for programmed death-ligand 1 (PD-L1), pembrolizumab, an immune checkpoint inhibitor can be used as a treatment, and it was found to improve overall survival. However, there are only a few reports on the relationship between the therapeutic effects of pembrolizumab in patients with lung cancer and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…A total of 20 studies assessed HRs of PFS in the meta-analysis [ 6 , 13 19 , 21 27 , 30 34 ]. The results showed that PFS was significantly improved for the occurrence of irAEs compared with non-irAEs (HR = 0.55, 95% CI = 0.51–0.60, p < 0.001; shown in Fig.…”
Section: Literature Source and Search Strategymentioning
confidence: 99%
“…A total of 20 studies assessed HRs of PFS in the meta-analysis [ 6 , 13 19 , 21 27 , 30 34 ]. The results showed that PFS was significantly improved for the occurrence of irAEs compared with non-irAEs (HR = 0.55, 95% CI = 0.51–0.60, p < 0.001; shown in Fig.…”
Section: Literature Source and Search Strategymentioning
confidence: 99%
“…Patients who discontinue ICI treatment due to irAEs have continued to experience treatment benefit, suggesting a potentially mechanistic association between irAEs and ICI efficacy, even with relatively short exposure . Exploratory, retrospective analyses of studies with anti–programmed cell death 1 (PD-1) agents nivolumab and pembrolizumab in NSCLC showed longer progression-free survival (PFS) among patients who experienced irAEs than in those who did not, and other ICI studies showed that overall survival (OS) was longer in patients with irAEs than in those without . Further evaluation of irAE occurrence as a predictive clinical biomarker for ICI response in NSCLC is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of reported irAEs in NSCLC varies widely, ranging from 24.0% to 70.5%. This reflects heterogeneity including in study setting (observational vs randomized clinical trial), patient characteristics (cancer stage, PD-L1 status, geographical location, race and ethnicity), treatment parameters (ICI agent used either alone or combined with chemotherapy, treatment line), and irAE grading . In our cohort, the incidence of clinically meaningful irAEs was 37.0%.…”
Section: Discussionmentioning
confidence: 96%
“…Demographic characteristics (age, sex, race, body mass index, and ECOG), concomitant medications (corticosteroids, proton pump inhibitors, and antibiotics), peripheral laboratory markers (hemoglobin, albumin, C-reactive protein, and others), tumor characteristics (histology, stage, PD-L1 expression, driver mutation status, and disease burden), and treatment-related factors (treatment line, response, ICI agent, concurrent chemotherapy, time to starting ICI, cumulative dose, and cumulative cycles of ICI) are inconsistently reported as predictive factors associated with irAE development. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]48,[60][61][62] In our cohort, we identified several baseline patient characteristics associated with irAE development: 60 years or older, ECOG performance status 0, high expression of PD-L1, absence of bone metastases, DNLR of 3 or less, and levels of hemoglobin, albumin, and LDH within reference range. Other than response to ICI therapy, irAE development was not associated with treatment-related characteristics (ICI agent, ICI alone or in combination with chemotherapy, and treatment line) in our study population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation